Beyond the Textbook: Komik AR Synergia dan Transformasi Pembelajaran Sumber Energi di Kelas V SD - Shonia Arum Kurniawati; Aan Nurfahrudianto; Jatmiko (YASIN, 2026)
The dominance of teacher-centered instruction and the limited use of interactive media constitute barriers to improving students’ learning outcomes in abstract Natural and Social Sciences (IPAS) content. This condition was evident among fifth-grade students at SDN Gondang 1, Bojonegoro Regency, only 48.3% of whom achieved learning mastery based on the Learning Objective Achievement Criteria (KKTP) score of 73 for energy sources content. This study aimed to develop the Augmented Reality (AR)-based SYNERGIA Comic and analyze its validity, practicality, and effectiveness in improving fifth-grade students’ learning outcomes in energy sources content. The study employed a research and development method using the 4D model, which comprised the define, design, develop, and disseminate stages, and was conducted at SDN Gondang 1 from February to July 2026. Product validation involved two validators, namely a subject matter expert and a media expert. Product trials were conducted through a limited trial involving 10 students and an extensive trial involving 24 students. Validity and practicality data were collected using a Likert-scale questionnaire consisting of 10 statement items, whereas media effectiveness was analyzed using N-gain scores. The results showed that the media achieved a subject matter validity level of 90% and a media validity level of 88%, both of which were categorized as highly valid. The practicality level reached 98% based on the teacher’s assessment, 94% based on students’ responses in the limited trial, and 97.08% in the extensive trial, all of which were categorized as highly practical. The mean N-gain score reached 0.91 in the limited trial and 0.80 in the extensive trial, both of which were categorized as highly effective, with classical mastery of 100% at both testing stages. Thus, the AR-based SYNERGIA Comic was declared valid, practical, and highly effective as an IPAS learning medium for energy sources content. These findings contribute to the development of technology-based learning in elementary schools and provide teachers with a practical alternative for helping students understand abstract scientific concepts within the context of the Kurikulum Merdeka.